2022
DOI: 10.1007/s00424-022-02770-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of the endothelial reverse mode sodium-calcium exchanger in the dilation of the rat middle cerebral artery during hypoosmotic hyponatremia

Abstract: A decrease in serum sodium ion concentration below 135 mmol L−1 is usually accompanied by a decrease in plasma osmolality (hypoosmotic hyponatremia) and leads to the disorder of intracranial homeostasis mainly due to cellular swelling. Recently, using an in vitro model of hypoosmotic hyponatremia, we have found that a decrease in sodium ion concentration in the perfusate to 121 mmol L−1 relaxes the isolated rat middle cerebral artery (MCA). The aim of the present study was to explore the mechanism responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…LP-1S might precisely enhance the regulation of Ca 2+ by PMCA1b and TRPV6 to reduce the intracellular Ca 2+ concentration and maintain an intracellular low calcium state, thus exerting an anti-PEDV effect ( Figure 10 ). Therefore, intracellular calcium homeostasis is particularly important to maintain normal cellular physiological functions and resistance to viral infection ( Klapczyńska et al, 2023 ; Sørensen et al, 2023 ). Overall, LP-1S significantly reduced the intracellular Ca 2+ concentration, whereas the increase in the extracellular Ca 2+ concentration suggested that LP-1S might exert its anti-PEDV effects mainly through Ca 2+ channel proteins that inhibit intracellular Ca 2+ in-flow and promote Ca 2+ out-flow ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…LP-1S might precisely enhance the regulation of Ca 2+ by PMCA1b and TRPV6 to reduce the intracellular Ca 2+ concentration and maintain an intracellular low calcium state, thus exerting an anti-PEDV effect ( Figure 10 ). Therefore, intracellular calcium homeostasis is particularly important to maintain normal cellular physiological functions and resistance to viral infection ( Klapczyńska et al, 2023 ; Sørensen et al, 2023 ). Overall, LP-1S significantly reduced the intracellular Ca 2+ concentration, whereas the increase in the extracellular Ca 2+ concentration suggested that LP-1S might exert its anti-PEDV effects mainly through Ca 2+ channel proteins that inhibit intracellular Ca 2+ in-flow and promote Ca 2+ out-flow ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%